CFD-DEM coupled with thermochemical sub-models for biomass gasification: Validation and sensitivity analysis. (18th May 2020) - Wang, Shuai; Luo, Kun; Fan, Jianren
Highlights: A reactive CFD-DEM model was developed on the open-source MFIX-DEM software. The model was validated with the experimental data and simulation results. The sensitivity analysis was conducted about contact and drag models. Abstract: A user-defined solver towards the high-fidelity CFD-DEM method with thermochemical sub-models integrating is developed based on the open-source MFIX-DEM software for simulating biomass gasification in a fluidized bed reactor. In this method, the fluid phase is solved under Eulerian framework while the solid motion is solved under Lagrangian framework. The inter-particle and inter-phase interactions, heat and mass transfer, gas turbulence, radiation, particle conversion, drying, pyrolysis, and homogeneous reactions are synthetically considered. The method is validated with experimental data and simulation results, and the sensitivity analysis is conducted for assessing the influence of contact and drag models on the CFD-DEM simulation of biomass gasification. Results show that the magnitude of total calculation time for the non-linear Hertzian contact model is 6.8 times of that for the linear LSD contact model. The drag models significantly affect the gas-solid flow dynamics while having a slight influence on the thermochemical results obtained at the reactor exit. As a result, the present work delivers a promising perspective for modeling thermochemical processes ( e.g., fast pyrolysis, coal combustion, iron smelting, and tablet coating) in dense reactive particulate systems by using the open-source MFIX-DEM software.